Evaluación del estado de conservación y potencial de los recursos en comunidades de la cuenca del bajo Ucayali, Distrito de Jenaro Herrera, 2015 - Panduro Saldaña, Erick (2015)
The research evaluated the use, conservation status and potential of natural resources in communities of the lower Ucayali basin, Jenaro Herrera district, Loreto region. Methodological instruments were used to collect qualitative information (surveys) and quantitative information (production data) through surveys in family units established in each of the communities of the study. Work was done with two communities: Nuevo Pumacahua with 11 surveys and Nuevo Aucayacu with 9 surveys. Conservation of resources is based on ancestral knowledge, using only what is sufficient and adequate to conserve the little that remains; the conservation of their forests and the use of lands without perennial vegetation such as the lowlands (planting vegetables) prevail. The potential of these communities lies in the existence of lakes near the community, where fish species can be protected; in the forests there are forest species to conserve as parent trees (seedbeds); and they have natural stands of camu camu in the Supay lake. The knowledge and recovery of the experiences of these people can be strengthened in the changes of attitudes and thoughts, in the way of producing and protecting resources, taking advantage of them today, but without forgetting the generations; improving their techniques will allow in the future to have thriving populations, with development and in harmony with their natural environment.